Processo penal de exceção - Lacerda, Fernando Hideo Iochida (2018)
The scope of this paper is to construct a critical theory of criminal procedure, capable of revealing the authoritarian essence hidden behind criminal garantism appearance of the penal power in the 2010s Brazilian society. The contemporary revival of authoritarian regimes calls, as a first step of democratic resistance, for understanding how tyrannical mechanisms work. In that regard, it was attempted to systematize a scientific penal model which weighs down the real and concrete world, revealing the fraudulent operations diluted in Brazil’s justice system democratic, institutional rhetoric. Fundamental concepts that emerge from Pedro Estevam Serrano’s theory of exceptional measures and liquid authoritarianism and Luigi Ferrajoli’s criminal garantism were adopted. By those scientific methods, this thesis proposes unveiling an emerging facet of authoritarianism blurred by justice enforcement and appearance of democratic routine. The criminal procedure of exception negates the ideal model of criminal garantism (democratic checks and balances tactics to limit penal power), debased in real, concrete authoritarian practices in the criminal justice system (tyrannical tactics of expunging the enemy). Slyly, those principles are assaulted by their antitheses, constituting what was systematized as the criminal procedure of exception. This works is a search for critical comprehension of truly authoritarian practices in the criminal justice system, an investigation aiming to unveil fraudulent expedients against the Federal Constitution, an impulse to awaken the resistance in the name of constitutional guarantees and popular sovereignty